Serum enzyme activities in blood and milk in the different stage of lactation in Holstein dairy cows - Đoković Radojica; Cincović Marko; Kurćubić Vladimir; Ilić Zoran; Lalović Miroslav; Jašović Boban; Petrović Miloš (Biotechnology in Animal Husbandry, 2017)
The objective of this study was to determine correlation between serum blood and milk enzyme activities of aspartate-aminotransferase (AST), alanine- aminotransferase (ALT), alkaline-phosphatase (ALP in the 36 dairy Holstein cows divided into three groups according to production period. Group 1 consisted cows in the start of lactation (n = 12); Group 2 -consisted of early lactation cows (n=12) and Group 3 included mid lactation cows (n=15). Statistically significant higher (P<0.01) activity of AST in blood serum was established in early lactation groups of cows as compared to mid lactation group of cows. ALT activity showed a lower (P<0.01) serum activities in early lactation groups of cows than in the mid lactation cows. Higher values ALP in blood and milk are determined in early lactation groups of cows as compared to mid lactation cows, but without statistical significance (P>0.05). Research results showed possibility of mild degree of hepatic lesions, probably due to fat infiltration in early lactation cows. No significant difference (P>0.05) was observed in milk serum value for AST, ALT and ALP between the three groups of cows. No significant correlations among AST, ALT and ALP activities in blood and milk serum were determined (P>0.05) and shows that activity of these enzyme in the milk are not used as markers for early diagnosis of subclinical metabolic disease.